Solvent-Free Lipase-Catalysed Esterification of Potato Maltodextrins - Magdalena Rudlicka; Arkadiusz Zarski; Marta Pokora-Carzynska; Janusz Kapusniak (Polysaccharides)
The aim of this research was to obtain new, ecological products with emulsifying properties based on potato maltodextrins and fatty acids and to prepare stable emulsions with the obtained esters as emulsifiers. The esterification of potato maltodextrin with different degrees of saccharification using oleic acid (model reaction) and free fatty acids from oil hydrolysis in the presence of lipases from Thermomyces lanuginosus and Aspergillus oryzae as biocatalysts was carried out. The reaction yielded products with degrees of substitution (DS) ranging from 0.017 to 1.35. Physicochemical analysis of the obtained products (FT–IR, NMR, morphological studies, and solubility measurements) was carried out. The occurrence of the reaction was confirmed, and the influences of the degree of saccharification of maltodextrin, the type of lipase used, and the reaction conditions on the degree of substitution obtained and the related product properties were evaluated. Oil-in-water emulsions were prepared on the basis of the obtained esters, which were then visually assessed. The lowest creaming index (0.0%) was obtained for the emulsion prepared from low-saccharified maltodextrin ester with DS = 0.038.